A construção da educação na revista Veja - Fonseca, Ana Paula Azarias da (2008)
This study analyzes the cover stories of Veja, a Brazilian weekly magazine, that focus on education . The corpus includes cover articles on education published between 1968-2006. The articles were divided into three thematic axes: school, family and brain/intelligence. This, however, was a methodological division as the axes are intertwined. Our analysis focused on the discursive constructions and strategies for production of meaning adopted by the enunciator when proposing communicative contracts to the reader. The conclusion of the analysis is that one must know to be able to tell one what to do . We analyzed similar thematic axes in different periods which allowed the contextualization of the articles relative to their respective social, political and historical scenarios. The study also analyzed the instruments and mechanisms employed by the enunciator to persuade the reader on what to do[CN1] , which is presented by the magazine in the form of modalizing primers//booklets//statements[CN2] . The study was based on the theories of discourse of Fiorin & Barros, Prado, Braga & Calazans, Mira, Scalzo and Germano among others. The basic analysis of the corpus was carried out based on discursive semiotics. The debate proposed by this study about education in the media aims to contribute to clarify issues arising from the intertwining of the fields of education and communication, as stated by Morin, which is only possible through the mediation and circulation of symbolic capital